Pengaruh kecerdasan emosi dan kecerdasan spiritual terhadap pola bercinta remaja di kalangan pelajar Sekolah Menengah Kejuruan (SMK) Negeri di Kota Samarinda, Kalimantan Timur, Indonesia - Jannah, Mishbahul (2013)
This study aims to determine the level of emotional intelligence, spiritual intelligence and its relationship with adolescent love pattern among Vocational High School students (SMK) at Samarinda, East Kalimantan, Indonesia. The study involved a total of 375 respondens comprised students from class X (ten) to XII (twelve). Questionnaires used in this study and consists of 4 parts. Part A covers the background of the respondents which include gender, age, grade and school name. Part B is a questionnaire USM Emotional Quotient-Inventory (USMEQ-i), a measure of emotional intelligence, while the C is a questionnaire on spiritual intelligence using intellegence Spiritual Big Scale Integrated (ISIS). Part D is the questionnaire “Inventori Pemilihan Pasangan”(IPP), which measures the pattern of teenage love. Data were analyzed using Statistical Package For The Social Sciences (SPSS 16.0). Descriptive analysisis used to answer the first objective, the second and third by using frequency, percentage, mean and standard deviation, and the use of intervention analysis to answer the fourth and fifth objectives of the correlation method. Findings showed that the most dominant emotional intelligence among students is emotional intelligence in terms of emotional control with M=25.65.In addition,the study also showed that the level of spiritual intelligence is the most dominant in terms of spiritual intelligence Trancendence (T) with M=95.08. Patterns are dominated by teenagers love aspects of property (HT) with M=27.09. The analysis showed a significant relationship between the aspects of emotional intelligence aspect of teenage love pattern property (HT), Lineage (KT), Beauty (KC), and Religion(AG) and there is a significant relationship between the aspects of the spiritual intelligence with teen dating patterns in terms of property (HT), Lineage (KT), and Religion(AG).